2015
DOI: 10.1007/s11695-015-1783-7
|View full text |Cite
|
Sign up to set email alerts
|

Elipse™, a Procedureless Gastric Balloon for Weight Loss: a Proof-of-Concept Pilot Study

Abstract: This pilot study demonstrates the safety and performance of Elipse™, a procedureless gastric balloon for weight loss. Future studies will test a commercial design filled to 550 mL intended to last in the stomach for at least 12 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 16 publications
(24 reference statements)
1
27
0
Order By: Relevance
“…At 6 weeks, the mean %EWL was 12.4%. One patient had the balloon endoscopically punctured owing to partial collapse, and one patient elected to have the balloon endoscopically removed; however, no serious adverse events occurred …”
Section: Space‐occupying Devicesmentioning
confidence: 82%
“…At 6 weeks, the mean %EWL was 12.4%. One patient had the balloon endoscopically punctured owing to partial collapse, and one patient elected to have the balloon endoscopically removed; however, no serious adverse events occurred …”
Section: Space‐occupying Devicesmentioning
confidence: 82%
“…A few studies have already proven the concept of a procedureless IGB. Machytka et al published the first report in 2016 [46] and a series of 34 cases one year later [47]. Such studies demonstrated good weight loss outcomes with a tolerable rate of adverse events.…”
Section: Elipsementioning
confidence: 99%
“…That pledge refers to the fact that no endoscopy is necessary for insertion or removal of the balloon. Yet, it requires fluoroscopy to certify the gastric position before inflation [46]. Allurion Technologies have had some exploratory attempts to exempt x-ray using portable ultrasound confirmation, but this is not FDA approved to date.…”
Section: Elipsementioning
confidence: 99%
“…The device is then completely deflated and the balloon is passed in the stool (33). One small study in the Czech Republic showed an EWL of 12.4% at 6 weeks, with no adverse outcomes reported (34). Another study showed improvements in LDL, triglycerides and HbA1c at 6 months.…”
Section: Intragastric Balloonsmentioning
confidence: 99%